2009
DOI: 10.1186/1471-2164-10-511
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of malformed umbilical cords from somatic cell nuclear transfer-derived piglets: implications for early postnatal death

Abstract: BackgroundSomatic cell nuclear transfer (scNT)-derived piglets have high rates of mortality, including stillbirth and postnatal death. Here, we examined severe malformed umbilical cords (MUC), as well as other organs, from nine scNT-derived term piglets.ResultsMicroscopic analysis revealed complete occlusive thrombi and the absence of columnar epithelial layers in MUC (scNT-MUC) derived from scNT piglets. scNT-MUC had significantly lower expression levels of platelet endothelial cell adhesion molecule-1 (PECAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 34 publications
(46 reference statements)
5
42
0
Order By: Relevance
“…Lee et al [18] assessed the global protein expression profiles in term placentas from SCNT pigs and found that the proteins closely involved in the apoptotic signaling pathway were different in comparison with controls. In malformed umbilical cords of SCNT piglets, proteins prevention of oxidative stress were downregulated, while molecules involved in apoptosis were upregulated [20]. In the present study, two novel proteins including HMG-CoA synthase were identified as common differences in the SCNT pigs.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Lee et al [18] assessed the global protein expression profiles in term placentas from SCNT pigs and found that the proteins closely involved in the apoptotic signaling pathway were different in comparison with controls. In malformed umbilical cords of SCNT piglets, proteins prevention of oxidative stress were downregulated, while molecules involved in apoptosis were upregulated [20]. In the present study, two novel proteins including HMG-CoA synthase were identified as common differences in the SCNT pigs.…”
Section: Discussionmentioning
confidence: 47%
“…Accordingly, many abnormalities observed in SCNT fetuses and offspring may be influenced by deficiencies in mitochondrial function. Recently, comparative proteomic analyses of SCNT piglets and placentae from SCNT pigs were reported [18][19][20]35]. Two-dimensional gel electrophoresis analysis revealed changes in the responses of several detoxification-related proteins to stress and inflammation in sudden death observed in SCNT piglets with extensive hepatopneumonic apoptosis [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MtDNA genotypes were determined by PCR-mediated single-strand conformation polymorphism analysis using the variable region of D-loop [6,7]. CA3 and CA4 exhibited a mixture of genotypes with D-mtDNA [79] more sequence variants in a cell, a genetic bottleneck in the female germ line will generally favor the transmission of a single mitochondrial population (homoplasmy) [13,27,28]. However, in SCNT animals both stable and unstable transmission of D-mtDNA was found in porcine and bovine G n s [10,17].…”
Section: Transmission Of Mitochondrial Dna In Cloned Cattle and Pigsmentioning
confidence: 99%
“…Two-dimensional differential gel electrophoresis (2D DIGE) is becoming more popular in protein quantification with the inclusion of an internal standard, providing a technology that greatly reduces experimental variation [74,75]. Recently, differentially expressed proteins of SCNT piglets and placentae from SCNT pigs and cattle were reported using comparative proteomic analyses [76][77][78][79]. We investigated the differences of protein expression profiles of mitochondria in adult SCNT pigs derived from Chinese pig (Meishan breed) fibroblasts and European pig enucleated oocytes (maternal Landrace breed) [17,29] using a 2D DIGE system [80].…”
Section: Mitochondrial Proteomic Approach In Cloned Cattle and Pigsmentioning
confidence: 99%